Adenopygus: a new genus and two new species of Luzarinae cricket of Brazilian Atlantic Forest (Orthoptera: Grylloidea) - Bolfarini, Marcio P.; de A. G. De Mello, Francisco (Zootaxa, 2012)
The aim of the present work is to describe Adenopygus, a new genus with two species of luzarine phalangopsid crickets from the Atlantic Forest on the Mantiqueira fault escarpment of southeastern Brazil.